Teaching and learning computer science sorting algorithms with mobile devices: A case study - Boticki, Ivica; Barisic, Ante; Martin, Sergio; Drljevic, Neven (Computer applications in engineering education, 2013)
In this article, we present a semester‐long study on using smartphone devices in computing engineering education. We developed Sortko, an Android‐based smartphone application for learning sorting algorithms, an important undergraduate computer science topic. The application consists of four main components—the module for interactive sorting, the scaffolding module, the motivational module, and the graphical user interface module, each with a distinct role of helping students in learning sorting algorithms. Our research methodology included data collection with administered two surveys, collected exam results and recorded application usage data. Analysis of the collected data shows our approach is an effective way of learning sorting algorithms. © 2012 Wiley Periodicals, Inc. Comput Appl Eng Educ 21:E41–E50, 2013